Genetic Modifiers of Duchenne Muscular Dystrophy in Chinese Patients - Chen, Menglong; Wang, Liang; Li, Yaqin; Chen, Yongjun; Zhang, Huili; Zhu, Yuling; He, Ruojie; Li, Huan; Lin, Jinfu; Zhang, Yu; Zhang, Cheng (Frontiers in Neurology, 2020)
Background Duchenne muscular dystrophy (DMD) is a fatal, X-linked recessive muscle disorder characterized by heterogeneous progression and severity. We aimed to study the effects of single nucleotide polymorphisms (SNPs) in SPP1 and LTBP4 on DMD progression in Chinese patients. Methods We genotyped LTBP4 haplotypes and the SPP1 promoter SNPs rs28357094, rs11730582, and rs17524488 in 326 patients registered in the neuromuscular database of The First Affiliated Hospital of Sun Yat-sen University. Kaplan-Meier curves and log-rank tests were used to estimate and compare median age at loss of ambulation, while Cox proportional hazard regression models were used as to analyze the effects of glucocorticoids treatments, DMD genotype, and SPP1/LTBP4 SNPs on loss of ambulation. Results The CC/CT genotype at rs11730582 was associated with a 1.33-year delay in ambulation loss (p = 0.006), with hazard ratio 0.63 (p = 0.008), in patients with truncated DMD genotype and undergoing steroid treatment. On the other hand, rs17524488 in SPP1 and the IAAM/IAAM haplotype in LTBP4 were not associated with time to ambulation loss. Conclusions SPP1 rs11730582 is a genetic modifier of the long-term effects of steroid treatment in Chinese DMD patients. Thus, any future clinical study in DMD should adjust for glucocorticoids use, DMD genotype, and SPP1 polymorphisms.